Innovative, paired careers tutorials: increasing the number of medical students choosing general practice as a career - Allsopp, Gail; Taggar, Jaspal (Taylor & Francis, 2018)
Background: With a crisis in general practice recruitment, to maintain the current workforce, the Department of Health and Social Care quote a need for 50% of our medical students to choose general practice as a career. There is much variety between medical schools and Nottingham University, alongside most others does not achieve this.